Penerapan ESG dalam Kinerja Perusahaan Secara Global - Saputra, Nathania Adeline (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Climate change and extreme temperature increases require business actors to implement ESG in their business activities. The implementation of ESG has an impact on company strategy, company performance, and consumer image of the company. According to the Global Sustainable Investment Alliance (GSIA) report, global ESG assets under management will reach 30.3 trillion by November 2023. The research results show that the implementation of ESG has a positive impact on company performance. This research uses secondary data collection methods using analytical media and literature reviews from existing journals. It is hoped that this research can provide new knowledge for business owners and readers and can be used by business actors globally.